2014
DOI: 10.1007/s00167-014-3016-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stability and kinematics of the natural knee versus a PS TKA with a ‘third condyle’

Abstract: The 'third condyle' TKA provides similar anteroposterior and mediolateral stability to the natural knee. This feature granted an adequate balance between laxity and constraint to reproduce natural joint kinematics, including smooth femoral rollback, without causing paradoxical external tibial rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In particular, internal rotation occurs at 0-30 • flexion by screw home rotation of the knee, which we have identified as internal moment. Additionally consistent with our findings, Zaggagnini et al [40], Wunschel et al [41], and Akbari et al [42] showed that tendencies of the anterior, medial translation, and internal rotation directions were similar in knee joints that had undergone TKA and did not exhibit VM impairment when compared with those of the native knee joint. However, the current study confirmed that the valgus moment generally occurred in knee joints that had undergone TKA, in contrast to the findings of previous studies [38,41,43,44].…”
Section: Discussionsupporting
confidence: 93%
“…In particular, internal rotation occurs at 0-30 • flexion by screw home rotation of the knee, which we have identified as internal moment. Additionally consistent with our findings, Zaggagnini et al [40], Wunschel et al [41], and Akbari et al [42] showed that tendencies of the anterior, medial translation, and internal rotation directions were similar in knee joints that had undergone TKA and did not exhibit VM impairment when compared with those of the native knee joint. However, the current study confirmed that the valgus moment generally occurred in knee joints that had undergone TKA, in contrast to the findings of previous studies [38,41,43,44].…”
Section: Discussionsupporting
confidence: 93%
“…With these navigation systems, data on varus-valgus and rotational profiles can be obtained during TKA surgery. Such intraoperative kinematic data might provide instructive clinical information for the refinement of surgical techniques, as well as information on the anticipated postoperative clinical outcomes [2,3,8,9,14,15,[18][19][20]25]. In addition, it is possible that the subjective medical examination in clinical practice could be performed objectively by using navigation.…”
Section: Introductionmentioning
confidence: 99%
“…Laxity and functional kinematics have been published in both the intact and implanted knee [ 1 , 5 , 8 , 9 , 12 , 14 , 15 , 24 , 25 , 35 ]; however, the effect of downsizing the femoral component and polyethylene insert on the knee’s laxity envelope is not well reported. Surgeons strive to restore function and feel of the unimplanted, healthy knee by matching native boney and soft tissue anatomy with the TKA component options available [ 19 , 26 ].…”
Section: Introductionmentioning
confidence: 99%